PENGARUH ENVIRONMENTAL PERFORMANCE TERHADAP ENVIRONMENTAL DISCLOSURE DAN HARD ENVIRONMENTAL DISCLOSURE PERUSAHAAN - Gladia, Prima; Rahardja, Surya (Diponegoro Journal of Accounting, 2013)
The objective of this study is to determine the impact of environmental performance to the level of environmental disclosures and the level of hard environmental disclosures. Disclosure is scored using an index developed by Clarkson et al. (2008) and the environmental performance measure is based on PROPER ratings. The population in this study is non-financial companies listed on Indonesia Stock Exchange in 2011. Based on purposive sampling criteria, obtained 61 companies as a sample. Analysis of the hypothesis testing in this study using statistical analysis (linear regression analysis and t-test). From the result obtained by testing the first hypothesis that the environmental performance has a significant positive affects on the level of environmental disclosure. Test result on the second hypothesis that the environmental performance has not significantly influences to hard environmental disclosure.